Social vrangorden i klassisk bramisk samfundslære - Aktor, Mikael (Religionsvidenskabeligt Tidsskrift, 1994)
This article is an investigation of the concept of varnasamkara, the mixing of the four orders of the classical Indian social hierarchy. The concept is described as both a fictive 'explanation' of the origin of those tribal castes, which gradually were included in the social system, and as a reflection of an actual practice of sexual relations across the barriers of the orders. Particularly the pratiloma-relations, the hypogamous relations between men of lower orders with women of the upper orders, are brought into focus. These relations in genealogical as well as other sorts of interaction are finally analyzed in the light of Victor W. turner's concept of antistructure to show why the Brahmin householders, who were explicitly engaged in the affairs of the world, showed contempt for these relations, while the world-renouncers, whether Brahmin or Buddhist, viewed them in a more positive light.